Does Telecommuting Reduce Commuting Emissions? - Waldemar Marz; Suphi Sen (Center for Economic Studies and ifo Institute (CESifo), 2021)
The long-term trend toward more work from home due to digitization has found a strong new driver, the Covid-19 pandemic. The profound change in urban mobility patterns supports the often-held view that reducing the number of commuting trips can lower carbon emissions to a certain degree. We investigate this optimistic view from a long-run perspective in a monocentric urban model with household-level vehicle choice based on fuel efficiency. In the medium run, fewer trips lead to the choice of less fuel-efficient vehicles. In addition, with lower annual driving costs to the city center, households change their location in the long run toward longer commuting trips, but cheaper housing, implying an adjustment in the real-estate market. These changes in vehicle choice and the urban form largely eliminate the initial environmental benefits. Binding fuel economy standards completely prevent the medium-run drop in fuel efficiency, but slightly exacerbate the long-term increase in commuting trip length.
Keywords: H23; L90; Q48; R40; 330; telecommuting; monocentric city; fuel economy; carbon emissions